Evaluasi Rekam Medis Elektronik RS Bethesda Yogyakarta Dalam Upaya Mendukung Percepatan Transformasi Kesehatan Digital - Darsono, Darsono (Divisi SIMKES, HPM, Fakultas Kedokteran, Kesehatan Masyarakat, UGM, 2024)
Background: One of the digital transformation efforts in hospitals is to implement standardized electronic medical records that can have data exchange capabilities. It is important to evaluate the extent to which electronic medical records are implemented in hospitals.Methods: Mixed method research with a sequential explanatory case study was conducted at Bethesda Hospital from September to October 2023. Primary data collection used digital maturity index instruments, variable checklists and RME meta data as well as in-depth interviews. Instrument completion involved 14 respondents, consisting of hospital management, users, IT teams and medical records. Data analysis was done descriptively.Results: In an effort to support the acceleration of digital health transformation, Bethesda Hospital has pioneered a computerized system starting in 1992, and built SIMRS starting in 2012. The digital maturity level of the Hospital Digital Maturity Assessment survey is 4 in 2023, which means managed collaboration. The depth of use of EMR has been accommodated in SIMRS, the suitability of EMR Emergency Department variables and meta data obtained a figure of 32% variables and meta data exist in accordance with KMK. 46% of variables and meta data exist but are not in accordance with KMK, and 22% of variables and meta data do not exist as in KMK guidelines. Three barriers to the implementation of RME were identified, including internal and external policies, infrastructure and human resources. Bethesda Hospital prioritizes patient care, based on regulations related to RME, for services and claims.Conclusion: Bethesda Hospital has implemented the acceleration of digital health transformation with SIMRS starting in 2012. In the year 2023 Hospital Digital Maturity Assessment survey, the result of the maturity level is 4, which means managed collaboration, the organization has used hospital information systems according to their structure and function as well as established policies and procedures. The depth of use of EMR has been accommodated in SIMRS, however the hospital still needs to adjust to the variables and meta data standardized by the Ministry of Health. Keywords: SIMRS, EMR, Health Transformation